POTENSI PENGGUNAAN KITOSAN RANTAI PENDEK SEBAGAI PEMBAWA DALAM PENGHANTARAN GEN; EVALUASI IN VITRO - Winarti, Lina; Martien, Ronny; Sismindari, S (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
Gene therapy involves the introduction of DNA or ribonucleic acid (RNA) into the target cell either to express or suppress the biosynthesis of proteins. The success of gene therapy is highly dependent on a suitable carrier system that can efficiently deliver genes in to specific desired cell with minimum cytotoxicity on target cells. Chitosan is interesting to be used as a gene carrier because it has a high positive charge and low toxicity to cells. Positive charge chitosan can form complexes with the plasmid. DNA complexes provide protection against enzymes degradation and promote internalization of plasmids that have been condensed. In this study the complex formation of chitosan-pEFneo-GFP and chitosan / TPP-pEFneo-GFP is by complex coaservation method. The results of complex analysis with a 0.8% agarose gel electrophoresis for 30 minutes 100Volt showed that the complex was stayed in the well and the plasmids did not migrate like plasmids which were dissolved in the water and buffer solvent. Stability evaluation in storage at room temperature for 14 days showed that the complex with chitosan concentration 0.02%-0.04% were the most stable, so that transfection analysis performed for the complex with chitosan concentration of 0.02%-0.04%. Transfection results showed that chitosan is able to protect plasmid and promote the internalization of plasmid into the nucleus and then expressed as a green luminescence. From these results chitosan potentially be developed as a carrier system in gene delivery.